Normative values for relative schoolbag weight in primary school children aged 6-14 from Czech Republic: A pilot study - Kasović, Mario; Štefan, Lovro; Zvonar, Martin (PLoS One, 2019)
Little evidence from observational studies has been provided regarding 'optimal' relative schoolbag load during primary education. Also, no study to date has provided reference-based standards for relative schoolbag weight. Therefore, the main purpose of the study was to establish normative values of relative schoolbag weight in a sample of children. In this cross-sectional study, we recruited 584 primary school students aged 6-14 (meanage±SD = 9.6±2.4 yrs, meanheight±SD = 1.4±0.2 m, meanweight±SD = 37.5±13.3 kg, meanbody-mass index±SD = 17.6±3.1 kg/m2, 44.4% girls) chosen from five schools in the city of Brno. Schoolbag weight and child's body weight were objectively measured by using digital scale. Relative schoolbag weight was calculated by dividing schoolbag weight with child's body weight and the result was expressed in percentage. Lambda, Mu and Sigma (LMS) method was used to create sex- and age-percentile curves. Boys carried slightly heavier schoolbag, compared with girls (mean difference 0.2 kg, p = 0.020). No significant differences between sexes in relative schoolbag weight were observed (p = 0.240). Median values (P50) for boys and girls were similar and the largest observed between ages 6-9 in boys (15-17%) and 6-8 in girls (16-18%). The percentage of children carrying relative schoolbag weight beyond 10% of their body weight was very high, especially between ages 6-10 in boys (85.1-100%) and 6-11 in girls (86.8-95.4%). This study provides first sex- and age- relative schoolbag weight normative values in primary school children. Future studies should use similar methods for generating comparable data.
Keywords: Students; Female; dítě; Weight-Bearing; ženské pohlaví; průřezové studie; Adolescent; zatížení muskuloskeletálního systému; lidé; Pilot Projects; pilotní projekty; školy; Schools; Sex Factors; Cross-Sectional Studies; Male; sexuální faktory; Czech Republic; index tělesné hmotnosti; Česká republika; Child; studenti; mužské pohlaví; Body Mass Index; mladiství; Humans